Managerial incentives and the efficiency of capital structure - Joseph P. Hughes; William W. Lang; Choon-Geol Moon; Michael S. Pagano (Rutgers University, Department of Economics, 2001)
We extend the literature on the effects of managerial entrenchment on capital structure to consider how safety-net subsidies and financial distress costs interact with managerial incentives to influence capital structure in U.S. commercial banking. Using cross-sectional data on publicly traded, highest-level U.S. bank holding companies, we find empirical evidence of Marcus' proposition (1984) that there are dichotomous strategies for value maximization—one involving relatively higher financial leverage and the other, lower financial leverage. As Marcus notes, midrange policies sacrifice value. We show that a less levered capital structure is associated with a higher charter value— better growth opportunities and market power—and vice versa. Moreover, we provide evidence that differences in charter value result in dichotomous strategies for managerial entrenchment: under-performing, less levered firms hold too little capital while under-performing, more levered firms hold too much. To explain this additional result, we develop a theoretical model that considers the effect of better market opportunities on incentive-conflicted managers' consumption of perquisites and on their use of defensive capital strategies to protect their job tenure and perquisites.
Keywords: D24; G21; G32; 330; agency problems; capital structure; charter value; corporate control; efficiency; Kapitalstruktur; Führungskräfte; Ökonomischer Anreiz; Prinzipal-Agent-Theorie; Bank; Allokationseffizienz; Theorie; Unternehmenswert